Shocks and Household Welfare in Sudan - Etang Ndip, Alvin; Touray, Sering (World Bank, Washington, DC, 2021)
The Sudanese economy has faced several shocks over the years, sometimes resulting in devastating impacts on the economy and the welfare of Sudanese households. The sources of these shocks vary, ranging from weather-related shocks such as droughts and floods to the global financial crisis and commodity price hikes. In the absence of effective social protection programs, exposure of households to frequent shocks lowers their ability to escape poverty, pushing households slightly above the poverty line back into poverty and sliding poor households deeper into poverty. This paper applies this framework to examine the impact of shocks on the welfare of Sudanese households and explore coping strategies typically utilized by households to mitigate the negative effects of shocks. The paper uses the 2009 National Baseline Household Survey (NBHS) and the 2014-15 National Household Budget and Poverty Survey (NHBPS) to document the main types of shocks that Sudanese households are exposed to and describe the profile of Sudanese households likely to be vulnerable and/or resilient to shocks. To complement this analysis, the paper uses the most recent round of the data collected in 2014/15 (containing information on idiosyncratic shocks) together with data on covariate shocks such as rainfall and conflict obtained from other sources to estimate the impact of shocks on household welfare. Since the impact of shocks on household welfare is likely to be multidimensional, various indicators of household welfare such as consumption, poverty status, assets, dietary quality, and diversity are considered in the paper. Results from the analysis are used to highlight the state of social protection in Sudan and discuss the need for an expansion of the existing system.